Máximo Orrios: a photojournalist in Madrid in the early decades of the 20th century - Panadero Peropadre, Nieves (Revista General de Información y Documentación, 2023)
Spanish photojournalism emerged with force in the years of the Second Republic and was consolidated during the Civil War. However, by the 1920s and even before that decade photography had gradually replaced engraving in magazines and “illustrated” newspapers due to its greater immediacy and adherence to reality. Many of the figures responsible for that change are now just names beneath their photographs, among them that of Máximo Orrios. The present text sets out to discover the man behind that signature and to offer the first analysis of his work as a whole. Orrios, who was in his thirties at the start of the 20th century, engaged in various professions and had many hobbies, including photography. His evolution from Pictorialism to photojournalism and from amateur to professional not only defines him but also many of his unknown colleagues. Putting him and them under the spotlight has been the principal objective of this study.